An efficient protocol for in vitro regeneration from the nodal explants of Withania coagulans (Stocks) Dunal: a valuable medicinal herb - Pari DEHVARI-NAGAN; Hosein ABBASPOUR; Mohammad Hasan ASARE; Sara SAADATMAND (Acta Agriculturae Slovenica)
In order to develop a protocol for the effective micropropagation of the important medicinal plant Withania coagulans (Stocks) Dunal, the effects of different concentrations and combinations of growth regulators on the nodal explants in two independent experiments were investigated. For shooting, a MS medium fortified with different concentrations and combinations of IBA (0.01, 0.1 and 0.5 mg l-1), BA (0.5, 1 and 2 mg l-1), Kin (0.5 and 1 mg l-1), PG (0.5 mg l-1) and GA (0.5 mg l-1) was used and the highest shooting response, shoot number and shoot length were obtained in the MS + IBA (0.01 mg l-1) + BA (0.5 mg l-1) + PG (0.5 mg l-1) + GA (0.5 mg l-1) treatment. In the second experiment, the effect of MS supplemented with different combinations and concentrations of IBA (0.1, 0.5, 1 and 2 mg l-1), NAA (0.1 and 1 mg l-1) and PG (1 mg l-1) on rooting of the nodal explants was investigated, which showed that the highest rooting response (%) was observed in the MS fortified with NAA (0.1 mg l-1), NAA (1 mg l-1), NAA (0.1 mg l-1) + PG (1 mg l-1), and NAA (1 mg l-1) + PG (1 mg l-1) treatments, as well as the highest number of roots at NAA (0.1 mg l-1) and the highest root length at IBA (1 mg l-1). Our findings highlight a complete micropropagation method for W. coagulans from the nodal explant that can make a significant contribution to the development of W. coagulans material for medical applications.